Experimental study on the viscosity-temperature characteristics and rheological properties of offshore heavy oil. (22nd April 2020) - Cao, Meng; Cheng, Linsong; Huang, Shijun; Xue, Yongchao; Du, Mengge; Yang, Yanwei; Xia, Yun; Chen, Xiao
The viscosity-temperature characteristics and rheological properties of heavy oil were investigated experimentally. Experimental results indicate that viscosity is sensitive to temperature, and it is a binary function of temperature and shear rate meeting preferably Arrhenius equation. In addition, the semi-log curve of viscosity-temperature can be divided into three regions and there is no obvious turning point, which exhibits that the internal microstructure of heavy oil during the heating process changes gradually. Besides, activation energy of low temperature range is higher than that of high temperature range. Moreover, the heavy oil always behaves as Newtonian fluid when temperature is higher than crystallisation temperature. Furthermore, on condition that temperature is less than crystallisation temperature, the heavy oil behaves as pseudo-plastic fluid characterising shear thinning phenomenon when shear rate is less than critical shear rate, and it presents as Bingham fluid with yield stress when shear rate falls between 10 and 50 s −1 . [Received: March 16, 2018; Accepted: October 24, 2018]